Inactivation of chronic wasting disease prions using sodium hypochlorite. - Katie Williams; Andrew G Hughson; Bruce Chesebro; Brent Race (PLoS ONE, 2019)
Chronic wasting disease (CWD) is a fatal prion disease that can infect deer, elk and moose. CWD has now been detected in 26 states of the USA, 3 Canadian provinces, South Korea, Norway, Sweden and Finland. CWD continues to spread from endemic areas, and new foci of infections are frequently detected. As increasing numbers of cervids become infected, the likelihood for human exposure increases. To date, no cases of CWD infection in humans have been confirmed, but experience with the BSE zoonosis in the United Kingdom suggests exposure to CWD should be minimized. Specifically, hunters, meat processors and others in contact with tissues from potentially CWD-infected cervids need a practical method to decontaminate knives, saws and other equipment. Prions are notoriously difficult to inactivate, and most effective methods require chemicals or sterilization processes that are either dangerous, caustic, expensive or not readily available. Although corrosive, sodium hypochlorite (bleach) is widely available and affordable and has been shown to inactivate prion agents including those that cause scrapie, bovine spongiform encephalopathy and Creutzfeldt-Jakob disease. In the current study, we confirm that bleach is an effective disinfectant for CWD prions and establish minimum times and bleach concentrations to eliminate prion seeding activity from stainless steel and infected brain homogenate solutions. We found that a five-minute treatment with a 40% dilution of household bleach was effective at inactivating CWD seeding activity from stainless-steel wires and CWD-infected brain homogenates. However, bleach was not able to inactivate CWD seeding activity from solid tissues in our studies.